Experimental Efficiency of Single Pass Solar Air Heater - aboghrara, alsanossi; Shukra, Mohamed (Journal of Pure & Applied Sciences, 2023)
The solar heat collector with the impingement of jet lower plate (SAHJF) experimentally designed and operated with typical parameters obtained from theoretical analysis to contained the maximum efficiency of the performance of thermal transfer. Then it was developed by replacing the flat absorber by the corrugated absorber (SAHJC) to enhance the efficiency. The flow rate of mass was selected equal and more than the typical value and the intensities of the solar radiation were chosen equal and less than the typical value to investigate the effect of both on the thermal transfer efficiency for SAHJF and SAHJC. Since the system works with a short range of temperature, the temperatures recorded were sensitive and needed a large accuracy. Therefore, an analysis method was proposed and applied to the data to be sure that it reflects the variance of temperature with different operating parameters. The correlation of temperature difference between the outlet and the inlet air with different flow rate and different intensities of irradiation for SAHJF and SAHJC was presented and compared.